Foot and Ankle Fusions Indications and Surgical Techniques (Springer International Publishing, 2018)
This unique book is a focused and comprehensive presentation of common fusion procedures (arthrodesis) for the foot and ankle, including patient selection, pre-operative assessment, intra-operative decision-making, and post-operative assessment. Sensibly divided into sections on the ankle, hindfoot, midfoot, and forefoot, each chapter concentrates on a specific fusion procedure for each area, including both open and minimally invasive surgical techniques. The chapters open with an overview of the procedure, including relevant historical points, evaluation, and indications and contraindications, then provide a detailed description of the techniques themselves, including clinical pearls and pitfalls. Case material is included as well, providing real-world illustration of each technique. Since arthrodesis can have a permanent effect on the gait of the patient, the procedure needs to be planned and performed with the utmost care and attention. With that focus clearly in mind, Foot and Ankle Fusions is an excellent resource for orthopedic surgeons, podiatrists, residents and fellows.